Variation and genetic profile of milk fatty acids indices in dairy sheep - Banos, Georgios; Symeou, Pavlos C.; Tzamaloukas, Ouranios; Miltiadou, Despoina (My University, 2015)
Implications To improve lipid fraction in ovine milk and products thereby enhancing their nutritive value. Introduction The fatty acid (FA) composition of ovine milk, which is rich in fat, is important to human health since consumption of saturated FA (SFA) may increased risk of cardiovascular disease, while consumption of other lipids such as the conjugated linoleic acid or total polyunsaturated FA (PUFA) contributes to the prevention of atherosclerosis, osteoporosis, or cancer (WHO, 2002). Genetic variation is known to affect bovine milk FA content (Stoop et al., 2008) but such knowledge in sheep is very limited. The objectives of this study were to (i) estimate genetic and phenotypic variation and parameters for ovine milk FA unsaturation indices (ii) identify genetic variants at candidate genes putatively affecting the ovine milk FA content, and (iii) assess the effects of polymorphisms in candidate genes on milk FA. Material and methods A dataset was developed comprising 429 dairy sheep of the Chios breed raised in four flocks in Cyprus. All animals were milking ewes in their 1st to 7th lactation that had lambed in 2012-2013. Each ewe had an average of 1.5 records with information on the concentration of 37 FA from which seven indices were constructed: total SFA, short-chain FA (SCFA), medium-chain FA (MCFA), long-chain FA (LCFA), mono-unsaturated FA (MUFA), PUFA and total unsaturated FA (UFA). The entire coding region, the 5' and 3' UTRs, of the genes DGAT1, SCD, ACAA2 and LIPG was initially sequenced in 50 of these sheep to identify polymorphisms. DGAT1 and SCD were found to be monomorphic whereas ACAA2 and LIPG were polymorphic in this population. Subsequently, all 429 animals were genotyped for a total of eight single nucleotide polymorphisms (SNP) at three polymorphic exons: one SNP in ACAA2 exon 10, one in LIPG exon 1 and six in LIGP exon 10, all located on chromosome 23. Trait variation and the effect of each genomic position on each trait were assessed with a mixed model including the fixed effects of flock, year and season of lambing, age of ewe at lambing, lactation number and stage of lactation as well as the random effect of animal. Both genotype and SNP effects were tested, separately, with this model. Bonferroni correction for multiple testing was applied post-analysis. Statistical analyses were conducted with ASReml (Gilmour et al., 2009). Results Between animal variation was evident (P<0.05) for all FA indices and most specific FA, suggesting the presence of inherent differences amongst individual animals. The ratio of animal to phenotypic variance ranged from 0.28 to 0.64 (P<0.05) for the FA indices, the highest pertaining to PUFA. This ratio for specific FA ranged from 0.07 to 0.94 (highest for C17:1. None of the FA indices was statistically significantly affected by the studied loci. On the contrary, locus effects (P<0.05) were found on specific FA and are summarised in Table 1 (marginal solutions expressed as % of total fat in milk). Table 1 Significant (P<0.05) locus effects on specific fatty acids Fatty acid Locus MAF1 Effect2 Size3 C5:0 (Valeric acid) ACAA2 exon 10 0.47 (C) SNP additive (C>T) 0.03 C14:1 (Myristoleic acid) LIPG exon 10 0.08 (C) Genotype dominance (CC>AA=AC) 0.64* C16:1 (Palmitoleic acid) ACAA2 exon 10 0.47 (C) Genotype dominance (TT=CT>CC) 1.25 LIPG exon 10 0.08 (C) Genotype overdominance (AC>AA>CC) 1.30 C17:1 (Heptadecenoic acid) LIPG exon 1 0.02 (A) SNP additive (A>C) 0.47* C18:2n6c (α Linoleic acid) LIPG exon 10 0.08 (C) Genotype dominance (AA=AC>CC) 0.25 1Minor allele frequency (base in parentheses); 2Description of the effect; 3Marginal effect of genotype with highest value (% of total fat in milk); *Significant after Bonferroni correction Conclusion Individual animals exhibited significant variation in specific milk FA and FA indices, suggesting that classical selective breeding can be used to improve these traits. The three genes examined affected some of the traits of interest meaning that molecular information may be added to the breeding schemes for more effective management and improvement of specific milk fatty acid concentration. Acknowledgements Work was funded by the Cyprus Research Promotion Foundation and the European Structural Fund. References Gimour, A.R., Gogel, B.J., Cullis, B.R., and Thompson, R. 2009. ASReml User Guide Release 3.0. www.vsni.co.uk. Stoop, W.M., van Arendonk, J.A.M., Heck, J.M.L., van Valenberg, H.J.F, and Bovenhuis, H. 2008. Journal of Dairy Science. 91:385-394. WHO/FAO. 2002. Technical Report Series 916. World Health Organisation, Geneva, Switzerland.
Keywords: Fatty acid; Genetic profile